Self-passivated edges of ZnO nanoribbons: a global search. Issue 41 (13th October 2022) - Ding, Li-Ping; Tang, Yan; Shao, Peng; Zhang, Hui; Guo, Yi-Jin; Zeng, Jia-Hao; Zhao, Ya-Ru
Abstract : Three types of pristine edges, reconstructed edges and the band structures of 2D ZnO. Abstract : The edge structure of two-dimensional (2D) materials plays a critical role in controlling their growth kinetics and morphological evolution, electronic structures and functionalities. However, until now, the accurate edge reconstruction of ZnO nanoribbons remains absent. Here, we present results of a global search of ZnO edge structures having used the CALYPSO program combined with the density functional theory (DFT) method. In addition to a database of all the possible edge reconstructed structures of ZnO nanoribbons, the most stable edge reconstructed structures of armchair (ZnOAC ), O-enriched zigzag (OZZ ) and Zn-enriched zigzag edges (ZnZZ ) have been confirmed based on molecular dynamics (MD) simulation and bonding configuration analysis of atoms near the edges. The edge formation energies show that their stabilities depend on the chemical potential ( μ O ) and the concentrations ( ρ O ) of oxygen atoms. Interestingly, a highly stable ZnZZ edge exhibits a novel nanotube-like structure and metallic characteristics, while the most stable reconstructed OZZ edge, resembling the letter "T", exhibits a narrow direct band-gap. It is almost certain that their electronic properties are determined by the edge states.